Perinatal Maternal Mortality in Sickle Cell Anemia: Two Case Reports and Review of the Literature. (2nd November 2017) - Rizk, Sanaa; Pulte, Elizabeth D.; Axelrod, David; Ballas, Samir K.
Abstract: As outcomes of patients with sickle cell anemia improve and survival into adulthood with good quality of life and expectation of long-term survival becomes more common, challenges have developed, including issues related to reproduction. Pregnancy is frequently complicated in patients with sickle cell anemia with mortality up to 4.0%. Here we report maternal perinatal mortality in two women with sickle cell anemia who died post-partum due to acute chest syndrome (ACS), caused by bone marrow fat embolism and review the literature pertinent to this subject. Patient A was a 28-year-old woman with sickle cell anemia with multiple complications. At 30 weeks' gestation she developed hemolysis associated with poor placental function necessitating delivery by C-section. The fetus was delivered successfully but she died due to multi organ failure after delivery. Autopsy showed pulmonary and amniotic fluid embolization. Patient B was a 37-year-old woman with uncomplicated sickle cell anemia who presented with pre term labor and crisis, then ACS and fetal distress. The infant was delivered successfully but the patient died after cardiovascular collapse. Autopsy results showed fat and bone marrow embolization as the cause of death. Pregnancy continues to be high risk for patients with sickle cell anemia including those with mild disease. Maternal perinatal mortality could be unpredictable due to serious complications of sickle cell disease. More studies to assess maternal perinatal mortality are needed.